2008
DOI: 10.1248/bpb.31.1928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Electroconvulsive Seizures on Spontaneous Alternation Behavior and Locomotor Activity in Rats

Abstract: Epileptic patients are at a significantly higher risk for impairments of cognitive function and behavioral abnormalities. In this study, we investigated the effect of repeated electroconvulsive shock (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Related to this, previous studies have been demonstrated that repeated ECS treatment reduced immobility time in the FST (Porsolt et al 1977;Li et al 2006), and 1 group also showed that repeated ECS treatment increased locomotor activity in the open field test (Hidaka et al 2008). These results suggest that ECS treatment increases energy expenditure under stressful conditions.…”
Section: Effect Of Repeated Ecs On Body Weight and Antidepressant-likmentioning
confidence: 53%
“…Related to this, previous studies have been demonstrated that repeated ECS treatment reduced immobility time in the FST (Porsolt et al 1977;Li et al 2006), and 1 group also showed that repeated ECS treatment increased locomotor activity in the open field test (Hidaka et al 2008). These results suggest that ECS treatment increases energy expenditure under stressful conditions.…”
Section: Effect Of Repeated Ecs On Body Weight and Antidepressant-likmentioning
confidence: 53%
“…Repeated ECSs could cause spatial‐learning deficits in the Morris water maze task following a 2‐month recovery period in rats (Lukoyanov et al,2004). Another study (Hidaka et al,2008) showed that repeated ECSs significantly impaired spontaneous alternation and increased locomotor activity, and behavioral changes induced by repeated ECSs persisted for at least 28 days. These findings may be related to neurogensis or apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…The alternation score was calculated as the ratio between actual alternations and possible alternations (defined as the total number of arm visits minus 2), multiplied by 100. This calculation was only performed for rats making more than fifteen arm visits ( Hidaka et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%